Feasibility of Cultivating Nutmeg (Myristica fragrans Houtt) in Sulamadaha Village, Ternate City, North Maluku Province - La Kamisi, Haryati; Tupamahu, Yonette Maya; Purimahua, Sarlotha Y ulliana; Apituley, Margaretha Rosalyn (Agrikan Jurnal Agribisnis Perikanan, 2023)
This study aims to determine the cash flow and feasibility of nutmeg cultivation based on the Net Present Value, Internal Rate of Return, Net B/C Ratio, Payback Period, and Break Even Point. The variables studied to determine cash flow are investment costs, operational costs, and revenues. This study uses a descriptive analysis method with a type of survey method. Respondents were taken by means of a census of 20 farmers. Primary data was obtained from direct interviews with respondents using questionnaires and secondary data was collected by documenting data from other sources. The results showed that the total costs used in nutmeg farming for 10 years on a land area of 0.5 ha was IDR 23,707,950.00 consisting of investment costs of IDR 1,182,950.00, operational costs of IDR 22,525,000.00, and receipts of IDR 654,381,000.00. The results of the investment analysis show that nutmeg farming is feasible based on the NPV value of IDR 349,136,600.00 which is greater than 0, the IRR value is 85.35% which is greater than the applicable loan interest rate (7%), and the value of the Net B/C Ratio is 33.68 which is greater than 1, the Payback Period is achieved within 7 years and the Break Even Point will occur in the seventh year